Asia-Pacific nations in international peace support and stability operations - Aoi, Chiyuki; Heng, Yee-Kuang (Asia today, 2014)
The eastward shift of political and economic power has been accompanied by increasing interest and participation in international peace support and stability missions by Asia-Pacific countries. From rising giants such as China and Indonesia to newer contributors such as Cambodia and the tiny city-state of Singapore, this book provides a first-ever cross-regional comparison of the capabilities of Asia-Pacific countries to contribute to peace support missions, with an eye to identifying strengths, weaknesses, emerging trends and policy implications. --Provided by publisher